(untitled) (REVISTA IBEROAMERICANA DE CIENCIAS EMPRESARIALES Y ECONONOMÍA, 2021)
This study discusses the challenge of sustainable growth through the green economy by conducting a bibliographical analysis of the concept’s application in the state of São Paulo, Brazil. Great challenges have been emerging in the globalized market and one of them is sustainable development. By observing this new market reality, companies, governments and people have been searching for new ways to advance economic growth. The new concept created to better define today’s economy is called green economy or low-carbon economy, which not only takes into account environmental protection but also conscientious consumption, social inclusion and sustainable production. Building a society that exerts less pressure on the planet’s natural resources is the biggest challenge of the century. Future generations will judge us by this legacy. Our attitudes towards the environment are not a waste of time, but can help transform the world into a sustainable place. To do so, such attitudes have to tackle the economy that we are used to: a system based on profit and growth, which frequently disregards the enviroment. This is where the concept of economic growth becomes relevant to evenly scale the environment and its preservation. However, is it posible to use this new way of sustainable thinking in all sectors of the economy? How can we invest in a green economy without economic loss? This research draws on data from the literature in order to answer these questions. It deploys both a quantitative and qualitative analysis, including an interview with the Secretary of Environment of the state of São Paulo.